2019
DOI: 10.1002/ima.22374
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of disc bulge and disc desiccation in lumbar MRI using concatenated shape and texture features with random forest classifier

Abstract: Disc bulge and disc desiccation are the most common abnormalities occurring in the spine, which leads to severe low back pain. Despite computer-aided automatic abnormality diagnostic imaging systems are available still there is a need for betterment in diagnostic accuracy and in processing time. Image processing with combined imaging features like shape and texture has given better diagnostic ability when compared with processing with individual features. In the present study, the desiccated and bulged Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…27 Ghosh et al 26,27 used the latter 2 methods in identifying degenerated disk disease on T2weighted midsagittal MRI scans-both achieving impressive results. Following work by Oktay et al 25 used a SVM on a substantially larger data set and found that their SVM method outperformed the 2 methods used by Ghosh et al 26,27 Later approaches used ML methods to classify degenerated disks along self-defined criteria 29 or the "gold standard" Pfirrmann grading criteria. 28,36 Sundarsingh and Kesavan 29 developed a fully automated system that identified and classified intervertebral disks on T2 MRI as "normal," "bulging," or "desiccated" through a combination of feature detection methods and ML classifiers.…”
Section: Diagnosis Of Degenerative and Traumatic Spinal Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Ghosh et al 26,27 used the latter 2 methods in identifying degenerated disk disease on T2weighted midsagittal MRI scans-both achieving impressive results. Following work by Oktay et al 25 used a SVM on a substantially larger data set and found that their SVM method outperformed the 2 methods used by Ghosh et al 26,27 Later approaches used ML methods to classify degenerated disks along self-defined criteria 29 or the "gold standard" Pfirrmann grading criteria. 28,36 Sundarsingh and Kesavan 29 developed a fully automated system that identified and classified intervertebral disks on T2 MRI as "normal," "bulging," or "desiccated" through a combination of feature detection methods and ML classifiers.…”
Section: Diagnosis Of Degenerative and Traumatic Spinal Pathologiesmentioning
confidence: 99%
“…Later approaches used ML methods to classify degenerated disks along self-defined criteria 29 or the “gold standard” Pfirrmann grading criteria. 28,36 Sundarsingh and Kesavan 29 developed a fully automated system that identified and classified intervertebral disks on T2 MRI as “normal,” “bulging,” or “desiccated” through a combination of feature detection methods and ML classifiers. Ruiz-España et al 36 developed a semiautomatic system that used gradient vector flow to grade degenerated disks, achieving “almost-perfect” agreement with a human expert (Cohen kappa of 0.81).…”
Section: Applications Of Discriminative Systems In the Spinementioning
confidence: 99%
“…They emphasize in their article that although disc swelling and disc desiccation, abnormalities in the spine that cause severe low back pain, are computer‐assisted automatic abnormality diagnostic imaging systems available, there is still a need for improvement in diagnostic accuracy and processing time 14 . In this study, dried and swollen Intervertebral Discs (IVDs) are automatically diagnosed by combining shape features extracted using Histogram of Oriented Gradients (HOG) and tissue features extracted using new Local Sub‐Rhombus Binary Relationship Model (LS‐RBRP) techniques.…”
Section: Reviewmentioning
confidence: 99%
“…They emphasize in their article that although disc swelling and disc desiccation, abnormalities in the spine that cause severe low back pain, are computer-assisted automatic abnormality diagnostic imaging systems available, there is still a need for improvement in diagnostic accuracy and processing time. 14 In this study, dried and swollen Intervertebral Discs (IVDs) are automatically diagnosed by combining shape features extracted using Histogram of Oriented Gradients (HOG) and tissue features extracted using new Local Sub-Rhombus Binary Relationship Model (LS-RBRP) techniques. In the paper, the performance analysis projects that the RF with HOG+LS-RBRP has an overall better accuracy of 94.7% when compared with HOG (87%) and LS-RBRP (90.2%) with the RF classifier separately in categorizing the normal IVD, disc bulge, and disc desiccation in the lumbar spine MRI.…”
Section: Reviewmentioning
confidence: 99%
“…MRI images were mainly used to acquire shape and texture features in in vivo measurements. Mayerhoefer et al [ 16 ], Hung et al [ 17 ], and Sundarsingh et al [ 18 ] made efforts in the analysis of the parameter sensitivity. Their studies confirmed that texture features and geometric parameters were sensitive to posterior disc bulging and, thus, can be used as quantitative biomarkers that predict disease.…”
Section: Introductionmentioning
confidence: 99%